Plasmodium falciparum Gametocyte-Specific Antibody Profiling Reveals Boosting through Natural Infection and Identifies Potential Markers of Gametocyte Exposure - Skinner, Jeff; Huang, Chiung-Yu; Waisberg, Michael; Felgner, Philip L.; Doumbo, Ogobara K.; Ongoiba, Aissata; Kayentao, Kassoum; Traore, Boubacar; Crompton, Peter D.; Williamson, Kim C. (Infection and immunity, 2015)
Malaria elimination efforts would benefit from vaccines that block transmission of Plasmodium falciparum gametocytes from humans to mosquitoes. A clear understanding of gametocyte-specific antibody responses in exposed populations could help determine whether transmission-blocking vaccines (TBV) would be boosted by natural gametocyte exposure, and also inform the development of serologic tools to monitor gametocyte exposure in populations targeted for malaria elimination. To this end, plasma was collected from Malian children and adults before and after the 6-month malaria season and probed against a microarray containing 1,204 P. falciparum proteins. Using publicly available proteomic data, we classified 91 proteins as gametocyte specific and 69 as proteins not expressed by gametocytes. The overall breadth and magnitude of gametocyte-specific IgG responses increased during the malaria season, although they were consistently lower than IgG responses to nongametocyte antigens. Notably, IgG specific for the TBV candidates Pfs48/45 and Pfs230 increased during the malaria season. In addition, IgGs specific for the gametocyte proteins Pfmdv1, Pfs16, PF3D7_1346400, and PF3D7_1024800 were detected in nearly all subjects, suggesting that seroconversion to these proteins may be a sensitive indicator of gametocyte exposure, although further studies are needed to determine the specificity and kinetics of these potential serologic markers. These findings suggest that TBV-induced immunity would be boosted through natural gametocyte exposure, and that antibody responses to particular antigens may reliably indicate gametocyte exposure.